PI-based PLL and 24-sector control of a 3P-3L-NPC inverter for grid-tied PV system synchronization - Sakina Ammari; Aziza Benaboud; Mohamed Talea (International Journal of Applied Power Engineering (IJAPE), 2022)
This article addresses one of the most serious issues in electricity: frequency and voltage anomalies. Actually, because renewable energy production is intermittent, the frequency and voltage of electricity produced are unstable and dependent on weather conditions. This issue causes industrial processes to fail, affecting the quality of the electrical supply and having a massive economic impact. Power electronics inverters are designed to compensate for system fluctuations in solar power generation. However, measurement noise in the grid voltage desynchronizes the inverter and network signals. The authors propose using a phase-locked loop technique based on inverter period control and a network voltage observer to achieve such synchronization of grid-connected photovoltaic (PV) systems. In this work, the grid integration of the PV system is carried out through a three-phase three-level neutral point clamped inverter due to better current quality with fewer harmonics and lower stress voltage of the inverter's components when compared to two-level voltage source inverters. The method is successfully applied in a simulated case study and experimental results validate it.